The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fpsyg.2018.00792
|View full text |Cite
|
Sign up to set email alerts
|

Re-entry Adjustment and Job Embeddedness: The Mediating Role of Professional Identity in Indonesian Returnees

Abstract: The present study examined the relationship between difficulty in re-entry adjustment and job embeddedness, considering the mediating role of sense of professional identity. The online data on demographic characteristics, difficulty on re-entry adjustment, sense of professional identity, and job embeddedness were collected from 178 Indonesian returnees from multiple organizations. The results showed that difficulty in re-entry adjustment was a significant predictor of a sense of professional identity; a sense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
0
4
0
4
Order By: Relevance
“…Data of the current study did not support this hypothesis and no significant association was observed between the two. Existing literature suggest mixed finding where some studies found a negative association between time since return and re‐entry problems (Andrianto et al, 2018; Yoshida et al, 2002), while other found no such association (Van Gorp et al, 2017). Based on the premise that shock‐related differences would depend on the time passed since arrival, this finding suggest conceptualizing it as a process requiring an open flexible time frame so as to see application of W‐curve model which was suggested by Gullahorn and Gullahorn (1963) identifying (re)acculturation as a process of numerous negotiation moments.…”
Section: Discussionmentioning
confidence: 99%
“…Data of the current study did not support this hypothesis and no significant association was observed between the two. Existing literature suggest mixed finding where some studies found a negative association between time since return and re‐entry problems (Andrianto et al, 2018; Yoshida et al, 2002), while other found no such association (Van Gorp et al, 2017). Based on the premise that shock‐related differences would depend on the time passed since arrival, this finding suggest conceptualizing it as a process requiring an open flexible time frame so as to see application of W‐curve model which was suggested by Gullahorn and Gullahorn (1963) identifying (re)acculturation as a process of numerous negotiation moments.…”
Section: Discussionmentioning
confidence: 99%
“…A construção da identidade profissional é um processo central para o desenvolvimento da carreira, pois orienta e direciona o comportamento dos indivíduos, em especial durante os períodos de transição (Andrianto et al, 2018). Por isso, torna-se um aspecto importante de ser avaliado no contexto das transições para o trabalho visto que se associa ao alcance de bons resultados na carreira (Oliveira, 2014).…”
Section: Discussionunclassified
“…Nas duas primeiras décadas do século XXI, as transições de carreira tornaram-se mais frequentes do que eram antes, o que exige dos indivíduos habilidades para mobilizar diferentes estratégias identitárias que sirvam como referências para a construção de projetos e planos de ação em um mundo dinâmico e instável (Ribeiro, 2014). Assim, o constructo identidade profissional passou a ser central para a compreensão do processo de construção da carreira, em especial durante os períodos de transição (Andrianto, Jianhong, Hommey, Damayanti, & Wahyuni, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…As Andrianto, Jianhong, Hommey, Damayanti, and Wahyuni (2018) shared their observation that the ability of an organization to retain the talented employees who have a great influence on the success of that organization is mutually favorable. The performance of an employee is a combination of capabilities, businesses, and opportunities that can be judged from their work (Andrianto et al, 2018). Employability has a great influence on working conditions; likewise, the Employability has an impact on the quality of education.…”
Section: Mediating Role Of Employabilitymentioning
confidence: 99%